PPARγ induces PD-L1 expression in MSS+ colorectal cancer cells - Gutting, Tobias; Hauber, Veronika; Pahl, Jens; Klapproth, Kay; Wu, Wenyue; Dobrota, Ioana; Herweck, Frank; Reichling, Juliane; Helm, Laura; Schroeder, Torsten; Li, Beifang; Weidner, Philip; et al. (OncoImmunology, 2021)
Only a small subset of colorectal cancer (CRC) patients benefits from immunotherapies, comprising blocking antibodies (Abs) against checkpoint receptor “programmed-cell-death-1” (PD1) and its ligand (PD-L1), because most cases lack the required mutational burden and neo-antigen load caused by microsatellite instability (MSI) and/or an inflamed, immune cell-infiltrated PD-L1+ tumor microenvironment. Peroxisome proliferator-activated-receptor-gamma (PPARγ), a metabolic transcription factor stimulated by anti-diabetic drugs, has been previously implicated in pre/clinical responses to immunotherapy. We therefore raised the hypothesis that PPARγ induces PD-L1 on microsatellite stable (MSS) tumor cells to enhance Ab-target engagement and responsiveness to PD-L1 blockage. We found that PPARγ-agonists upregulate PD-L1 mRNA/protein expression in human gastrointestinal cancer cell lines and MSS+ patient-derived tumor organoids (PDOs). Mechanistically, PPARγ bound to and activated DNA-motifs similar to cognate PPARγ-responsive-elements (PPREs) in the proximal −2 kb promoter of the human PD-L1 gene. PPARγ-agonist reduced proliferation and viability of tumor cells in co-cultures with PD-L1 blocking Ab and lymphokine-activated killer cells (LAK) derived from the peripheral blood of CRC patients or healthy donors. Thus, metabolic modifiers improved the antitumoral response of immune checkpoint Ab, proposing novel therapeutic strategies for CRC.
Gesehen am 07.06.2021